KINERJA KECAMATAN PEKANBARU KOTA DALAM PENYELENGGARAAN KEWENANGAN YANG DILIMPAHKAN TAHUN 2012-2013 - Vicky Haditanio; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Autonomy of Area through Rule Number 32 Year 2004 about the Government of Area just did not move most authorities from the Centre Government to the Regional Government but Rule Number 32 Year 2004 must bring the meaning for welfare of the people in the area that uptil now still could not be realised. As increase efforts in the public's service, delegation of the authority also really was needed in the optimisation of the achievement of the government for the sake of the achievement of the aim of the development and welfare.This research aimed at knowing the achievement of the Subdistrict Pekanbaru Kota in the implementation of the authority that was showered the year 2012-2013 and to know cause factors of the low level of the achievement of the Subdistrict Pekanbaru Kota in the implementation of the authority that was showered the year 2012-2013. This research used the qualitative approach with the type of the descriptive research. The process of the data collection was carried out in the Subdistrict-Head Pekanbaru Kota Office and the Mayor Pekanbaru Office part of General Administration Government. Where as the technique of the data collection consisted of the interview, document investigation, and observation with the data kind consisted of the primary data and the secondary data.From results of the research was attracted by the conclusion that the achievement of the Subdistrict Pekanbaru Kota in the implementation of the authority that was showered the year 2012-2013 as that was poured in the Rule Mayor Pekanbaru Number 11 year 2013 did not yet go optimal, was caused in the implementation of this authority not all the aspects of the authority were accompanied with the documentation, only took the form of the argumentation then. Cause factors of the low level of the achievement of the Subdistrict Pekanbaru Kota in the implementation of the authority that was showered the year 2012-2013 were the shortage of the Subdistrict Head's creativity, the shortage of human resources (human resources), the area of the territory and the number of inhabitants, the shortage of the capacity of document filing, the shortage of the work motivation, and the shortage of the utilisation of information and technology (IT).Keywords: Delegation of the Authority, the Achievement